PERANAN BIMBINGAN KONSELING “TRAUMA-INFORMED” UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA DI SEKOLAH DASAR - Rusnawati Ellis; Romi Kurniawan; Neleke Huliselan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science learning in elementary schools often faces challenges not only due to conceptual complexity but also because of psychosocial trauma that undermines students’ cognitive readiness—particularly in trauma-prone regions such as Eastern Indonesia. This study aims to examine the role of trauma informed guidance and counseling in enhancing conceptual understanding of Science (IPA) through a systematic literature synthesis. Employing a library research approach, 35 theoretical and empirical sources from international journals, books, and national policy reports were analyzed. Findings reveal that trauma informed counseling significantly supports IPA comprehension through three key mechanisms: (1) creating emotional safety that lowers the affective filter, (2) building self-efficacy through validation of lived experiences and small wins, and (3) fostering psychological resilience that transforms experimental failure into meaningful learning. These insights align with the Profil Pelajar Pancasila and underscore that inclusive science education must begin with psychological safety, not merely pedagogical innovation. The study recommends a structured collaboration between science teachers and school counselors as a strategic step toward humanizing education and advancing equity in learning outcomes.